2011
DOI: 10.4999/uhod.10015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Plasma Endostatin Levels in Patients with Acute Myeloblastic and Lymphoblastic Leukemia

Abstract: In this study, we evaluated the plasma levels of endostatin (PE) and its prognostic importance in patients with acute myeloblastic (AML) and lypmhoblastic leukemia (ALL). We therefore analyzed plasma levels of endostatin before the chemotherapy and during the complete remission period in adult ALL and AML patients. The PE levels of the control group were significantly lower than both cases with ALL and AML. The patients with AML during remission had significantly higher PE levels than the levels at initial dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…In addition, the dominant model, which groups these 2 subpopulations, suggests a similar behavior. The activity of COL18A1 rs2274808 was further validated by a study which determined that a defect in COL18A1 would change endostatin synthesis in a Salvadorian population (Mahajan et al, 2010 ), consequently leading to an antiangiogenic disorder, such as Knoblock syndrome and ALL; however, some authors have indicated that children with ALL have variable levels of endostatin (Dagdas et al, 2011 ), which makes it difficult to accurately explain its relationship with the disease (Schneider et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the dominant model, which groups these 2 subpopulations, suggests a similar behavior. The activity of COL18A1 rs2274808 was further validated by a study which determined that a defect in COL18A1 would change endostatin synthesis in a Salvadorian population (Mahajan et al, 2010 ), consequently leading to an antiangiogenic disorder, such as Knoblock syndrome and ALL; however, some authors have indicated that children with ALL have variable levels of endostatin (Dagdas et al, 2011 ), which makes it difficult to accurately explain its relationship with the disease (Schneider et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%